ANALISIS NILAI SETTING RELE DIFERENSIAL SEBAGAI PROTEKSI TRANSFORMATOR ADD ON BLOK 2 DI PT PJB UP MUARA TAWAR MENGGUNAKAN ETAP - Muhammad Fadhli Dzil Ikram; Moch. Dhofir; Teguh Utomo (Jurnal Mahasiswa TEUB, 2023)
This research discusses about the analysis of differential relay transformer setting as a protection for Add On transformer in PT PJB UP Muara Tawar at block 2 using Etap 19.01 simulation method and mathematical calculation according to IEEE Std 242-2001. Furthermore, to test the results of the setting calculations, a short circuit current calculation that occurs in the area in the protection zone and outside the protection zone is also carried out using the ETAP 19.01 simulation software. Based on the results of mathematical calculations and software simulations, the value of the short circuit current that occurs is 74346 A for 3-phase short-circuit, 58691 A for 2-phase short-circuit, and 67607 A for 1-phase short-circuit to ground in the primary area. And in the secondary area is 1630 A for 3 phase short circuit fault, 1376 A for 2 phase short circuit fault, and 67607 A for 1 phase short circuitfault to ground. Furthermore, the calculation results for the setting current and the differential are 0.313 A or 0.3 pu, along with a slope 1 value of 45.58% and slope 2 of 91.17%. Based on these results it can be concluded that the differential relay settings on the Add On transformer meet the established standards. Keywords : Differential Relay Transformer (87T), Etap, setting analysis